2009
DOI: 10.1152/physiolgenomics.00089.2009
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression endpoints following chronic waterborne copper exposure in a genomic model organism, the zebrafish, Danio rerio

Abstract: Craig PM, Hogstrand C, Wood CM, McClelland GB. Gene expression endpoints following chronic waterborne copper exposure in a genomic model organism, the zebrafish, Danio rerio. Physiol Genomics 40: 23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 67 publications
4
16
0
Order By: Relevance
“…While fish can habituate to some chronic stressors, sustained plasma cortisol levels similar to those used in this study have been observed in response to diverse stressors of anthropogenic and natural origins. For example, chronic exposure to aluminum, copper, selenium or low environmental pH can result in prolonged elevations in plasma cortisol levels (Craig et al 2009, Wiseman et al 2011, Kennedy & Picard 2012, Grassie et al 2013. In salmonids, sustained increases in cortisol levels are also associated with social subordination (Gilmour et al 2005) and with specific phases of the life cycle such as smolting (Nilsen et al 2008) and sexual maturation (Fuzzen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While fish can habituate to some chronic stressors, sustained plasma cortisol levels similar to those used in this study have been observed in response to diverse stressors of anthropogenic and natural origins. For example, chronic exposure to aluminum, copper, selenium or low environmental pH can result in prolonged elevations in plasma cortisol levels (Craig et al 2009, Wiseman et al 2011, Kennedy & Picard 2012, Grassie et al 2013. In salmonids, sustained increases in cortisol levels are also associated with social subordination (Gilmour et al 2005) and with specific phases of the life cycle such as smolting (Nilsen et al 2008) and sexual maturation (Fuzzen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These changes may be the result of a common generalized stress response in fishes to metal ion toxicity (Craig et al, 2009) or in response to systemic hypoxia as a result of impaired gas transport at the gills. Increases in Hct and Hb could occur to elevate the blood oxygen carrying capacity (Larsson et al, 1985;Cyriac et al, 1989) and to increase extraction at the gills.…”
Section: Hematological Parametersmentioning
confidence: 99%
“…Indeed, corticosteroids are believed to be endocrine regulators of some immune components and mechanisms in the short term (Kawano et al 2003;Esteban et al 2004). In contrast, chronic toxic exposure may be linked to long-term activation of the corticotropic axis (Craig et al 2009), reflected by immunosuppression. Furthermore, there is evidence for molecular interactions between the sex-steroid pathways and the corticotropic axis in fish (Milla et al 2009).…”
Section: Future Directionsmentioning
confidence: 99%